2000
DOI: 10.3141/1717-05
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Risk of Wet-Pavement Accidents: Fuzzy Logic Model

Abstract: Researchers developed a fuzzy-logic model for predicting the risk of accidents that occur on wet pavements. Preventing wet-pavement accidents has been an extremely difficult and elusive task because they are stochastic events whose occurrence is related to a variety of factors, including vehicle, roadway, human, and environmental characteristics. Conventionally, researchers use linear or nonlinear regression models and probabilistic models to predict wet-pavement accidents. However, these models often are limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 4 publications
0
19
0
3
Order By: Relevance
“…At the Pennsylvania Transportation Institute, Xiao et al (2000) found that the safety condition, measured by the percent reduction in wet-pavement accidents, could be improved nearly 60% if the skid number increased from 33.4 to 48.…”
Section: Previous Studiesmentioning
confidence: 98%
“…At the Pennsylvania Transportation Institute, Xiao et al (2000) found that the safety condition, measured by the percent reduction in wet-pavement accidents, could be improved nearly 60% if the skid number increased from 33.4 to 48.…”
Section: Previous Studiesmentioning
confidence: 98%
“…Past researchers have clarified some aspects of the heavy vehicle skidding accidents during emergency braking require the knowledge of wheel lock-up (Vangi & Virga, 2007;Xiao, Kulakowski, & EI-Gindy, 2000). In fact, the skidding phenomenon of a vehicle under braking is identified by the occurrence of wheel lock-up.…”
Section: Wheel Lock-upmentioning
confidence: 99%
“…In other words, the number of accident numbers change as a result of the road surface conditions. Xiao et al [17] have showed that rising of road surface skid resistance value from 35% to 48% makes a 60% decrease in traffic accidents.…”
Section: Evaluation Of Previous Studies and The Importance Of Skid Rementioning
confidence: 99%